Application of lean manufacturing technology in a milk manufacturing company - Morakinyo Kehinde Onifade; Olufemi Adebayo Oroye (Universitas Serang Raya, 2021)
This work presents the application of lean management principle in the area of waste elimination in a powder milk plant of a production company. The existing manufacturing procedure for the company’s plant was evaluated, and a lean manufacturing technique was developed for the plant. To achieve this, a time series analysis was carried out on the econometric data obtained, and a future forecast predicting losses and usage was predicted based on the practised manufacturing procedures. The econometric linear transfer function technique applied to the actual usage and actual loss data obtained filtered the waste in the production process and generated forecast values for actual loss and usage. This revealed that there had been poor manufacturing practices in the factory. The findings from this research can be used as a guide to managers on wastage control in a production system.